SUMBANGSIH CENDIKIAWAN DALAM PENERJEMAHAN BUKU-BUKU ILMU PENGETAHUAN (STUDI PADA MASA PEMERINTAHAN DINASTI ABBASIYAH) - Erna Kurniawati (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2019)
Abbasid dynasty is one dynasty that has a high civilization in the field of knowledge, of course this is inseparable from the efforts made by the caliph Harun Ar-Rasyid and Al-Ma'mun to translate the works that civilizations want to watch in the field of science, with the help of translators who have capabilities in foreign mastery languages. About the purpose of this article is to map the names of figures who had a major contribution to the development of science during the Abbasid Dynasty. By using the theory made as a knife of analysis in this study, the reasons for policies are decisions taken by people who have a budget to set a matter in accordance with the desired goals. While for this researcher will use the method of library analysis from various sources related to the history of Islamic civilization, both from books, research journals and related literature, to then be mixed and analyzed, conclusions are also obtained. Thus the results of this study indicate that the movement of translators of knowledge books does have an interesting interest for translators who come from outside the city of Baghdad also outside of Islam, to come translating special books, in order with the rewards and awards given by the caliph out of proportion to their hard work.